Comparison of the Total amount of Macrophages on Full Thickness Wound Bed in The Use of Tulle, Freeze-Dried Amnion, and Microbial Cellulose - Saktrio Darmono S.1, Beta Subakti Nata’atmadja1, David Sontani Perdanakusuma1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The wound is the most frequent problems faced by plastic surgeon. Many factors can affect the wound healing process. Macrophages are as one indicator of wound healing which present in the wound within 24-48 hours after injury. Currently, there is a variety of wound dressing available which can increase the levels of macrophages in the wound healing process according to previous research. Objectives: To compare the total amount of macrophages on full thickness wound bed in the use of tulle, freezedried amnion, and microbial cellulose on the second day. Material and Method: The study design was experimental, post-test only group design using 21 male rats Rattus norvegicus. The wound was closed with tulle, amnion, and microbial cellulose which was evaluated on the second day. The samples wounds were fixed by 10% formalin solution then examination of samples was conducted by Wright-Giemsa staining routine/Hemato-eosin under a microscope. Results: Macrophages obtained at a given tulle ranges between 41-96, freeze-dried amniotic at 51-142, and the microbial cellulose at 55-96. In other hand, the mean number of macrophages in the wound by the microbial cellulose at 77.4; its 1.3 times higher than the given tulle at 59; meanwhile its 0.9 times lower than the freeze-dried amniotic given by 83. Conclusions: There were no differences in the increase number of macrophages in the wound bed by the use of tulle, freeze-dried amnion and microbial cellulose on the second day.